The wireless application protocol : writing applications for the mobile internet - Singhal, Sandeep; Bridgman, Thomas; Suyranarayana, Lalitha; Manuey, Daniel; Chan, Jim.; Bevis, David; Hild, Stefan; Alvinen, Jari. ([S.l.] : Addison Wesley Longman, 2001)
The Wireless Application Protocol (WAP) will liberate the Web from wires, enabling anywhere/anytime access to virtually any data or application. In this book, leaders of the WAP standards process present the most complete discussion of the new WAP 1.1 standards, architecture, specification, and application development. This book gives decision-makers the information they need to plan strategies, and developers the information they need to build solutions -- starting today. It begins with an overview of WAP 1.1, describing the motivation behind the standards, and the relationships between each component of the WAP specification. Next, it discusses each component, covering fundamental design principles and operations. The book delivers in-depth guidance for developing WAP applications, covering user interface design, push messaging, the XML-based Wireless Markup Language (WML), scripting with WMLScript and WTAI, and more.